PAHLAWAN MINANGKABAU DALAM SENI LUKIS - Jasri Nova; Ismanadi Uska; Nurzal Zai (Universitas Negeri Padang, 2012)
Abstract This thesis aims to telling the story of the fighters who have fallen and aimed to revitalize the service to the present heroes who have forgotten history. in this case I think that the portrait depicts minangkabau hero, the next generation will remember kenbali about heroes struggle, because the current generation will not forget the history of both struggle and heroes. the struggle of the heroes who have risked their body and soul, from generation generation ker then finally on the date August 17, 1945 Ir.sukarno and Mohammad proclaimed the independence of Indonesia. This is the culmination of the freedom fighters during the previous centuries many nations fallen warriors and the goal of independence. Kata kunci : Pahlawan, Minangkabau, seni, lukis